Testicular ultrasound examination and hemodynamics of patients with azoospermia - M. Z. Vorobets; O. V. Melnyk; R. V. Fafula; O. K. Onufrovych; A. T. Borzhievsky; Z. D. Vorobets (Regulatory Mechanisms in Biosystems, 2022)
The most difficult form of male infertility to treat is azoospermia. Azoospermia is defined as the complete absence of spermatozoa in the ejaculate. The age of the patients who underwent clinical and diagnostic studies varied between 22 and 45 years. Among 119 examined patients with azoospermia, 58.0% were diagnosed with secretory infertility. In 42.0% patients, the presence of spermatogenesis in excretory-obturational infertility was established. Among 69 patients with secretory infertility, 23 had azoospermia in the absence of spermatozoa and spermatogenic cells, which accounted for 33.3% of all patients with secretory infertility (in particular, 2 with leukocytospermia, which indicated damage to the tubular apparatus as a result of previous orchitis). In 66.6% patients, azoospermia was observed in the absence of spermatozoa, but in the presence of precursor cells of spermatogenesis. 11.5% patients out of 69 (group 1) were diagnosed with concomitant diseases. We see that arterial hypertension, diseases of the gastrointestinal tract, liver, and kidneys occur. Hereditary diseases were not detected in the examined patients. Pain of varying intensity was found in 6.7% of patients, varying degrees of testicular hypoplasia were found in 7.6%, dysuria in 13.4%, epididymitis in history 8.4%; history of epidemic mumps 6.7%; 12.6% had depression, restlessness, sleep disorders, and 21.0% had erectile dysfunction. According to clinical examination and ultrasound, chronic prostatitis is suspected in 19.2% of patients. An increase in the number of leukocytes in the blood was found in 13.2% patients. According to ultrasound, 60.5% of the patients with azoospermia had normal testicular sizes, and 39.5% had reduced testes. The volume of the testicles in the control group was 22.3 ± 2.1 cm³ on average, varying from 18.3 to 25.1 cm³. In the group with azoospermia, the volume of the testicles was on average 16.7 ± 1.7 cm³ and varied from 8.2 to 21.1 cm³, that is, the volume of the testicles in patients with azoospermia was on average 1.3 times smaller compared to normozoospermia. In the obstructive form of azoospermia, diffuse changes were detected in both testicles, probably obturational changes. Hypoplasia of the left testicle and increased echogenicity were observed in the non-obstructive form of azoospermia. The veins of the spermatic cord were moderately dilated. There was a normal amount of free fluid in the scrotum. According to elastography, the elasticity of the testicles was above normal. Obturational processes in the testicles were suspected. The hemodynamic parameters of testicular parenchymal blood flow in infertile men obtained by ultrasound dopplerography are of important diagnostic value. The average value of the linear blood flow velocity in the arteries of the parenchyma in men with normozoospermia was 0.107 ± 0.015 m/s on the right, and 0.103 ± 0.012 m/s on the left. With azoospermia, the average value of the linear velocity of blood flow on the right was 0.086 ± 0.012 m/s, and on the left – 0.084 ± 0.008 m/s. Thus, the hemodynamic indicators of the scrotum show that the most pronounced changes are found in men with azoospermia in the absence of spermatogenesis.